2018
DOI: 10.1155/2018/5147585
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-Induced Neuroplasticity in the Circadian System

Abstract: Seasonal changes in light exposure have profound effects on behavioral and physiological functions in many species, including effects on mood and cognitive function in humans. The mammalian brain's master circadian clock, the suprachiasmatic nucleus (SCN), transmits information about external light conditions to other brain regions, including some implicated in mood and cognition. Although the detailed mechanisms are not yet known, the SCN undergoes highly plastic changes at the cellular and network levels und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 135 publications
2
23
0
3
Order By: Relevance
“…Because of an athlete’s chronotype (degree to which an individual is naturally a 'morning' or 'evening' person), timing of training or competition may not align with their personal time of peak performance 130–132. Persistent circadian dysregulation may contribute to neurodegeneration and mental health disorders 133–135…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…Because of an athlete’s chronotype (degree to which an individual is naturally a 'morning' or 'evening' person), timing of training or competition may not align with their personal time of peak performance 130–132. Persistent circadian dysregulation may contribute to neurodegeneration and mental health disorders 133–135…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…Unfortunately, the phase difference of VIP and AVP signaling is difficult to specify. The available data on rhythms of VIP and AVP and their receptors are quite heterogeneous as reviewed in [22, 66]. Furthermore, the phases depend on the developmental stage, on light input, and on day-length [28, 30, 67].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SAD, seasonal changes in photoperiod provoke relapse into a depressive episode [11]. SAD may be caused by SCN-mediated alterations of circadian rhythmicity which perturb the affective state [12]. Although not detected by GWAS after strict correction for multiple comparisons, associations between individual clock gene polymorphisms and mood disorders have been found in a number of studies have not revealed associations to clock genes, in targeted genotyping studies, e.g.…”
Section: Humansmentioning
confidence: 99%